2009
DOI: 10.3136/fstr.15.203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Flow Properties of Thickener Solutions and Their Velocity through the Pharynx Measured by the Ultrasonic Pulse Doppler Method

Abstract: The effect of viscosity µ of thickener solutions on their velocity through the human pharynx measured using the ultrasonic pulse Doppler method was investigated to develop an index for thickener solutions used as foods for dysphagic patients. The B-type viscometer determined an approximated value of viscosity at a selected shear rate γ · . The maximum velocity V max of water, which is often aspirated into trachea of patients with dysphagia, was about 3 times higher than that of yogurt, which is rarely aspirate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 14 publications
8
52
0
Order By: Relevance
“…However, the corresponding (average) value of a shear rate can be calculated with the B-type viscometer (Mitschka, 1982). Kumagai et al (2009) indicated that the viscosity measured with two types of viscometers, i.e., the B-type and cone-and-plate viscometers, coincided considerably well at the same shear rate. The B-type viscometer is widely used in Japan because it is cheaper than the cone-and-plate viscometer and is easy to operate.…”
Section: Sensory Evaluation Of Ease Of Swallowing and Stickinessmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the corresponding (average) value of a shear rate can be calculated with the B-type viscometer (Mitschka, 1982). Kumagai et al (2009) indicated that the viscosity measured with two types of viscometers, i.e., the B-type and cone-and-plate viscometers, coincided considerably well at the same shear rate. The B-type viscometer is widely used in Japan because it is cheaper than the cone-and-plate viscometer and is easy to operate.…”
Section: Sensory Evaluation Of Ease Of Swallowing and Stickinessmentioning
confidence: 99%
“…It was determined that the relationship between the time during which the bolus front moved from the middle to the inferior pharynx and the viscosity of non-Newtonian fluids was approximate to that of Newtonian fluids, whose viscosities range from 10 to 1,000 mPa·s, if the non-Newtonian fluid viscosity was evaluated for the characteristic shear rate of 100 s -1 under a liquid bolus volume of 30 mL in a vertical direction. However, it was reported that 10 − 30 s -1 is the best shear rate (Kumagai et al, 2009;Tashiro et al, 2010a). As this was based on the evaluation of different regions, using 10 s -1 as reported by Kumagai et al (2009) in our study would mean that the rank order from low to high viscosity would be: No.…”
mentioning
confidence: 99%
See 3 more Smart Citations